2018
DOI: 10.1002/lary.27570
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the glucocorticoid receptor alters SMAD signaling in vocal fold fibroblasts

Abstract: Objectives/Hypothesis Direct glucocorticoid (GC) injection for vocal fold (VF) scarring has evolved as a therapeutic strategy, but the mechanisms underlying the antifibrotic effects remain unclear. GCs act via the glucocorticoid receptor (GR), which is phosphorylated at multiple serine residues in a hormone‐dependent manner to affect bioactivity. We hypothesize that GCs regulate SMAD signaling via GR phosphorylation in vocal fold fibroblasts (VFFs). Study Design In vitro. Methods Human VFFs were treated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 34 publications
6
23
0
Order By: Relevance
“…We, therefore, sought to elucidate potential interactions between TGF-β and GC signaling to provide insight into clinical variability with the ultimate goal of optimized therapeutic efficacy. Previously, our laboratory immunolocalized the GC receptor (GR) in the vocal fold mucosa in vivo 12 and in our human vocal fold fibroblast cell line with an emphasis on three major serine phosphorylation sites within the N-terminal region of the receptor involved in transcriptional regulation (Ser 203 , Ser 211 , and Ser 226 ) 11 . In response to dexamethasone, Ser 211 localized predominately to the nucleus 11,13,14 .…”
mentioning
confidence: 99%
“…We, therefore, sought to elucidate potential interactions between TGF-β and GC signaling to provide insight into clinical variability with the ultimate goal of optimized therapeutic efficacy. Previously, our laboratory immunolocalized the GC receptor (GR) in the vocal fold mucosa in vivo 12 and in our human vocal fold fibroblast cell line with an emphasis on three major serine phosphorylation sites within the N-terminal region of the receptor involved in transcriptional regulation (Ser 203 , Ser 211 , and Ser 226 ) 11 . In response to dexamethasone, Ser 211 localized predominately to the nucleus 11,13,14 .…”
mentioning
confidence: 99%
“…Previous articles have demonstrated an antifibrotic effect of pirfenidone in which the level of p-Smad2/3 in the nucleus faded with pirfenidone treatment [11]. Mukudai et al [20] demonstrated that the mechanistic effect of steroids on vocal fold repair involves significantly altered Smad3 and Smad7 mRNA expression after steroid administration. Thus, this new discovery indicates that cisplatin may be an ideal antifibrotic agent for local application in patients diagnosed with laryngeal cancer who require CO 2 microsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…HVFFs were incubated with cisplatin at different concen-(For figure see next page.) trations (10,20,40,80, and 160 μΜ; Fig. 2a).…”
Section: Dose-and Time-dependent Antiproliferative Effect Of Cisplatimentioning
confidence: 96%
“…Conversely, Smad7 is a competitive inhibitor of Smad activation and is therefore thought to be antifibrotic. 31 Specifically, Smad3 is considered a master regulator of fibrosis. 32 Molecular signaling offers a new strategy to intervene in scar formation.…”
Section: Modulation Of Vf Fibrosis By the Tgf-β Familymentioning
confidence: 99%